Efectos de un programa de formación de padres para reducir conductas perturbadoras infantiles - Vives-Montero, Carmen; Cortes-Pendon, David; Lopez-Rubio, Sonia; Ascanio, Lourdes (Revista de Psicopatología y Psicología Clínica, 2017)
Abstract. Effects of a parent-training program to reduce children’s disruptive behaviors. This study evaluates the results of a parent training program incorporating some additional components to the traditional programs (emotional communication and problem solving) to be applied in the socio-community context. Eighteen parents comprised the control group and 21 the treatment group, with children 4 to 8 years old with disruptive behavior. The treatment group assisted to 7 sessions directed at improving parenting practices, registering their application and receiving feedback. Significant increases were found in the treatment group in parental use of appropriate discipline, incentives, and expectations. The treatment group reduced the application of severe discipline and the use of physical punishment, as well as the number and frequency of child behavior problems. The results persisted at the 1-year follow-up. Resumen. Este estudio evalúa los resultados de un programa de entrenamiento de padres aplicado en el contexto socio-comunitario que añade algunos componentes a los programas tradicionales (comunicación emocional y solución de problemas). Participaron 18 progenitores en el grupo control y 21 en el grupo de tratamiento con hijos de entre 4 y 8 años con conductas perturbadoras. El grupo de tratamiento asistió a 7 sesiones dirigidas a mejorar las pautas de crianza, registrar su aplicación y recibir retroalimentación. Se encontraron incrementos significativos en el grupo de tratamiento en la aplicación de disciplina apropiada, el empleo de elogios y las expectativas. El grupo de tratamiento redujo la aplicación de disciplina severa y el empleo del castigo físico y disminuyeron el número y la frecuencia de problemas de conducta de sus hijos. Los resultados se mantuvieron en el seguimiento un año después.